To the question of ethno-cultural policy of contemporary states - E. S. Karsanova (Управление)
At the end of 2010 - beginning of 2011 political leaders of Germany, Great Britain and France made statements for «a multiculturalism failure» that became a significant event in socio-political and ethnocultural life of Western Europe. Certainly, leaders of three leading countries of the European Union didn’t put into question the need of harmonious coexistence of representatives of various ethnocultures and religions in one state. They focused attention of the world community on incorrectly chosen principle of the organization of interaction of various ethnoconfessional and cultural communities living in the territory of the national state. Today practically everywhere the structure of modern national states loses the uniformity, and explosive forces of multiculturalism generate very serious political and sociocultural problems. Due to that we encounter with the question whether it is possible or not to find an adequate background to reach a unification of the civil and ethnic nation? This article is an attempt to answer this question.The analysis of trends in modern ethno-cultural policy in some European countries allows us to consider the dynamics undergoing ethno-political and sociocultural processes, in some cases as a solution to actual economic tasks and labor migration, in others - as a search for optimum ways of artificial creation of unified multicultural space.The conducted research allows to conclude that the declaration of the principles of multiculturalism doesn’t give a guarantee of achievement of interethnic tolerance, on the contrary, its functional application in a form of a certain formal technique, is obviously unpromising right where the target state policy is realized